Determination of Leaky SAW Propagation, Reflection and Coupling on LiTaO3 - Roesler, Ulrike; Cohrs, Dieter; Fischerauer, Gerhard; Dietz, A.; Ruile, Werner; Weigel, Robert (Ultrasonics Symposium Proceedings, 1995)
For the common LSAW cut 36°rotYX-LiTaO3 quantitative information about propagation, reflection and coupling has been theoretically determined with the Finite Element Method (FEM). The FEM results have been validated by both comparison with other theories and measurements. The electro-mechanical coupling coefficient k^2 and its dependence on metallization height, aperture and number of electrodes has been evaluated by measurement campaigns. We found k^2 values between 6 and 9%
elib2cris::1512001600,roesler1995